2008
DOI: 10.2147/ndt.s3381
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging investigations in Alzheimer’s disease: the resurgence of white matter compromise in the cortical dysfunction of the aging brain

Abstract: Diffusion tensor imaging (DTI) is a sophisticated MRI-based neuroimaging technique that enables in vivo quantifi cation of differences in molecular diffusion at the cellular level. Owing to the highly directional architecture of white matter (WM), DTI is providing important clues of the structure and geometric organization of this neural compartment. Since DTI can detect changes even in the case of radiologically "normal" appearing WM, researchers are using the technique for the study of WM integrity at the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 79 publications
5
30
0
Order By: Relevance
“…Regarding healthy elders, we observed that CR status was only related to WM integrity in the genum of the corpus callosum. According to previous literature (Medina and Gaviria 2008 and to our earlier DTI study whereby 'age related' and 'AD-typical' topography patterns of WM loss of integrity were reported (Bosch et al 2010b), effects to this area corresponds more to typical aging and are less characteristic of early dementia.…”
Section: Findings In Healthy Eldersmentioning
confidence: 73%
“…Regarding healthy elders, we observed that CR status was only related to WM integrity in the genum of the corpus callosum. According to previous literature (Medina and Gaviria 2008 and to our earlier DTI study whereby 'age related' and 'AD-typical' topography patterns of WM loss of integrity were reported (Bosch et al 2010b), effects to this area corresponds more to typical aging and are less characteristic of early dementia.…”
Section: Findings In Healthy Eldersmentioning
confidence: 73%
“…For example, in one report (Rose et al 2000), poorer MMSE score among AD patients was correlated with decreased diffusion anisotropy in the splenium of the corpus callosum. Among amnestic MCI patients and healthy age-matched controls, the same group reported that reduced FA in posterior white matter regions was associated with reduced cognitive performance, particularly in memory (Rose et al 2006;Medina and Gaviria 2008).…”
Section: Between Clinical Diagnostic Groupsmentioning
confidence: 94%
“…Finally, it might be straightforward to compare our HMM based paths to Diffusion Tensor Imaging (DTI) fibers, which has indeed proved a good tool for the diagnosis of AD [31,32]. Some could even argue that the resulting DTI tract reconstruction look similar to our computed paths (Figs.…”
Section: Discussionmentioning
confidence: 84%